2020
DOI: 10.12659/msm.922561
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of the Mammalian Target of Rapamycin (mTOR) Pathway Mediates the Effects of the Paeonol-Platinum(II) Complex in Human Thyroid Carcinoma Cells and Mouse SW1736 Tumor Xenografts

Abstract: Departmental sources Background: This study aimed to investigate the effects of the paeonol-platinum(II) (PL-Pt[II]) complex on SW1736 human anaplastic thyroid carcinoma cell line and the BHP7-13 human thyroid papillary carcinoma cell line in vitro and on mouse SW1736 tumor xenografts in vivo. Material/Methods: The cytotoxic effects of the PL-Pt(II) complex on SW1736 cells and BHP7-13 cells was measured using the MTT assay. Western blot measured the expression levels of cyclins, cell apoptotic proteins, and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Through serum pharmacochemistry, we identified 38 prototype components of "Scrophulariae Radix-Fritillaria" in the serum of the treated animals, of which cedrol, cis-ferulic acid, fetisinine, linolenic acid, paeonol, ussuriedine, 5-(methylsulfanyl)pentanenitrile, aucubigenin, and syringic acid were correlated to urine metabolites and may therefore be potential bioactive compounds. Ling et al found that the paeonol-platinum (II) complex promoted apoptosis of thyroid cancer cells, increased the fraction of sub-G1 cells, increased the expression of p27 and p21, downregulated p53 and cyclin D1, and inactivated the mTOR pathway in thyroid cancer cells (He et al, 2020). Panda et al demonstrated that syringic acid, a thyroid hormone receptor-β agonist, protected rats against PTUinduced thyroid toxicity by increasing the levels of T4 and T3; decreasing TSH, TNF-α, IL-6, ALT and AST levels; and improving the histological characteristics of thyroid tissues (Panda et al, 2021).…”
Section: Frontiers In Pharmacologymentioning
confidence: 99%
“…Through serum pharmacochemistry, we identified 38 prototype components of "Scrophulariae Radix-Fritillaria" in the serum of the treated animals, of which cedrol, cis-ferulic acid, fetisinine, linolenic acid, paeonol, ussuriedine, 5-(methylsulfanyl)pentanenitrile, aucubigenin, and syringic acid were correlated to urine metabolites and may therefore be potential bioactive compounds. Ling et al found that the paeonol-platinum (II) complex promoted apoptosis of thyroid cancer cells, increased the fraction of sub-G1 cells, increased the expression of p27 and p21, downregulated p53 and cyclin D1, and inactivated the mTOR pathway in thyroid cancer cells (He et al, 2020). Panda et al demonstrated that syringic acid, a thyroid hormone receptor-β agonist, protected rats against PTUinduced thyroid toxicity by increasing the levels of T4 and T3; decreasing TSH, TNF-α, IL-6, ALT and AST levels; and improving the histological characteristics of thyroid tissues (Panda et al, 2021).…”
Section: Frontiers In Pharmacologymentioning
confidence: 99%